pengaruh pruning dan konsentrasi pupuk gandapan maxima yang berbeda terhadap pertumbuhan dan hasil tanaman cabe keriting (capsicum annum l.) - Muhammad Muntazar*1; Nurrachman *2; Jayaputra *3 (CROP AGRO, Scientific Journal of Agronomy, 2019)
ABSTRACT This study aimed to determine the effect of pruning and fertilizer concentrations of Gandapan Maxima on growth and yield of Curly Chili (Capsicum annum L.). This research was conducted on July-October 2016 at Santong Village, Kayangan District, North Lombok Regency. The experimental design used factorial randomized block design (RCBD) with two factors. The first factor is the pruning consist of two levels, namely P1 (pruning) and P2 (unpruning). The second factor is the concentration of Gandapan Maxima fertilizer which consists of three levels, namely D1 (2 gr / l), D2 (3 gr / l), and D3 (4gr / l) The combinations was replicated three times, resulted 18 experimental units. Data were analyzed by ANOVA 5% and further test by Honestly Significant Different (HSD) at the level of 5%. The results showed that the interaction between pruning and fertilization concentration significantly affected fruit weight per plant only. The pruning treatment solely have a significant effect on plant height, number of leaves and fruit weight per plant, but did not significantly affect the number of branches and of fruits per plant. The treatment factor for fertilizer concentration has a significant effect on plant height, number of leaves and fruit weight per plant, but not significantly affected the number of branches and number of fruits per plant. The highest yield (576,5 gr/plant or 13,72 ton/hectare) achived by P1D1 ( Prunning and concentration 2 gr/l Gandapan Maxima).